1982
DOI: 10.1002/hlca.19820650523
|View full text |Cite
|
Sign up to set email alerts
|

Übergangsmetall‐katalysierte Additionsreaktionen von 3‐Phenyl‐2H‐azirinen und Acetylencarbonsäureestern

Abstract: Einen ganz anderen Verlauf nimmt die Umsetzung des Azirins 1 und Acetylendicarbonsaure-dimethylester in Gegenwart von Molybdanhexacarbonyl. Uber diese Reaktionen ist schon in einer vorlaufigen Mitteilung berichtet worden [4]; die vorliegende Arbeit enthalt erganzende Versuche und den vollstandigen experimentellen Teil. Molybdanhexacarbonyl-induzierte Additionen von 3-Phenyl-2H-azirinen undAcetylencarbonsaureestern. -Eine Losung von 2,2-Dimethyl-3-phenyl-2 H-azirin (1) und Acetylendicarbonsaure-dimethylester (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Intermolecular cycloaddition of π-systems with azirines represents another important class of reactions promoted by transition metal complexes. Heimgartner and co-workers showed that pyrroles 193 can be formed from azirines and alkynes under the influence of Mo­(CO) 6 (Scheme ) . A mechanism involving the formation of a azacyclobutene intermediate 194 and subsequent rearrangement was postulated by the authors.…”
Section: H-azirinesmentioning
confidence: 99%
“…Intermolecular cycloaddition of π-systems with azirines represents another important class of reactions promoted by transition metal complexes. Heimgartner and co-workers showed that pyrroles 193 can be formed from azirines and alkynes under the influence of Mo­(CO) 6 (Scheme ) . A mechanism involving the formation of a azacyclobutene intermediate 194 and subsequent rearrangement was postulated by the authors.…”
Section: H-azirinesmentioning
confidence: 99%
“…Importantly, the structure of 3a was unambiguously confirmed by X-ray crystal diffraction of its analogues 3h and 3w , revealing that the C–N bond of 2 H -azirine was cleaved in the reaction. It is interesting that the alkyne carbons are incorporated into the 2- and 3-positions of the pyrrole product rather than the 3- and 4-positions observed in the light-induced versions of this formal cycloaddition.…”
mentioning
confidence: 99%